2022
DOI: 10.1093/ejcts/ezac283
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve repair versus mechanical valve replacement for root aneurysm: the CAVIAAR multicentric study

Abstract: Aims Despite growing evidence that aortic valve repair improves long-term patient outcomes and quality of life, aortic valves are mostly replaced. We evaluate the effect of aortic valve repair versus replacement in patients with dystrophic aortic root aneurysm up to 4 years. Methods The multicentric CAVIAAR prospective cohort study enrolled 261 patients: 130 underwent standardized aortic valve repair (REPAIR) consisting of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The CAVIAAR prospective cohort study enrolled 130 patients who underwent aortic valve remodeling root repair with expansible aortic ring annuloplasty and 131 patients who underwent mechanical composite valve and graft replacement. 51 At 4 years, there was no statistically significant difference in the primary composite outcome of mortality, reoperation, thromboembolic or major bleeding events, endocarditis or operating site infections, pacemaker implantation, and HF between patients who underwent aortic valve repair or mechanical composite valve and graft replacement (HR, 0.66 [95% CI, 0.39–1.12)]. However, there were significantly fewer valve-related deaths (HR, 0.09 [95% CI, 0.02–0.34]) and major bleeding events (HR, 0.37 [95% CI, 0.16–0.85]) in patients who underwent aortic valve repair compared with those who underwent mechanical composite valve and graft replacement.…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…The CAVIAAR prospective cohort study enrolled 130 patients who underwent aortic valve remodeling root repair with expansible aortic ring annuloplasty and 131 patients who underwent mechanical composite valve and graft replacement. 51 At 4 years, there was no statistically significant difference in the primary composite outcome of mortality, reoperation, thromboembolic or major bleeding events, endocarditis or operating site infections, pacemaker implantation, and HF between patients who underwent aortic valve repair or mechanical composite valve and graft replacement (HR, 0.66 [95% CI, 0.39–1.12)]. However, there were significantly fewer valve-related deaths (HR, 0.09 [95% CI, 0.02–0.34]) and major bleeding events (HR, 0.37 [95% CI, 0.16–0.85]) in patients who underwent aortic valve repair compared with those who underwent mechanical composite valve and graft replacement.…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…However, most aortic valves are still replaced ( 3 ). The multicentric CAVIAAR study comparing aortic valve repair versus mechanical valve replacement for root aneurysm showed that standardized aortic valve repair with external annuloplasty significantly reduced valve-related deaths and major bleeding rates without increasing the risk of reoperation ( 4 ).…”
Section: Commentsmentioning
confidence: 99%